Comparative performance of early maturing maize cultivars developed in three Eras under drought stress and wellwatered environments in West Africa - Badu-Apraku, Baffour; Oyekunle, M.; Menkir, A.; Obeng-Antwi, K.; Yallou, C.; Usman, I.; Alidu, H. (Wiley, 2013)
Maize (Zea mays L.) is a major staple crop in West Africa and has the potential to mitigate the food insecurity in the subregion. However, maize grain yield is severely constrained by drought. A study was conducted at 13 locations in West Africa for 2 yr to determine genetic gains in yield of cultivars developed during three eras, 1988 to 2000 (first-generation cultivars), 2001 to 2006 (second-generation cultivars), and 2007 to 2010 (third-generation cultivars) under drought and optimal conditions. Under drought, yield ranged from 1346 kg ha?1 for first-generation cultivars to 1613 kg ha?1 for third-generation cultivars with a genetic gain of 1.1% yr?1. Under optimal conditions, yield gain ranged from 3363 kg ha?1 for first-generation cultivars to 3956 kg ha?1 for third-generation cultivars with genetic gain of 1.3%. The average rate of increase in yield was 14 and 40 kg ha?1 yr?1 under drought and optimum conditions. Genetic gains in yield from first- to third-generation cultivars under drought was associated with improved plant aspect and husk cover, whereas under optimum conditions it was associated with plant and ear aspects, increased ears per plant, plant and ear heights, and improved husk cover. Cultivars TZE-W DT C2 STR, DTE-W STR Syn C1, DT-W STR Synthetic, 2009 DTE-W STR Syn, and EV DT-W 2008 STR were high yielding and stable across drought environments. Substantial progress has been made in breeding for drought tolerance during the last three decades.